2012
DOI: 10.1007/s11325-012-0770-7
|View full text |Cite|
|
Sign up to set email alerts
|

Obstructive sleep apnea and acute myocardial infarction severity: ischemic preconditioning?

Abstract: Our study demonstrates that patients with OSA have less severe cardiac injury during an acute non-fatal MI when compared to patients without OSA. This may suggest a cardioprotective role of sleep apnea during acute MI via ischemic preconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
68
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 20 publications
9
68
1
4
Order By: Relevance
“…A potential cardioprotective role of intermittent ischemia from recurrent episodes of apneas during MI via preconditioning has been described 34. Although reduced myocardial injury verified by cardiac enzyme levels after MI in patients with OSA has been reported, untreated OSA may increase the risk of MI and recurrence of MI 4.…”
Section: Discussionmentioning
confidence: 99%
“…A potential cardioprotective role of intermittent ischemia from recurrent episodes of apneas during MI via preconditioning has been described 34. Although reduced myocardial injury verified by cardiac enzyme levels after MI in patients with OSA has been reported, untreated OSA may increase the risk of MI and recurrence of MI 4.…”
Section: Discussionmentioning
confidence: 99%
“…1-5 Up to 65% of patients who seek medical attention for a cardiovascular event are diagnosed with OSA. 1 There is a need to study OSA's ability to predict cardiovascular events; some cohort studies, following apneic patients, have identified a high number of fatal and non-fatal cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Results suggest that intermittent hypoxia could work as a protection factor for ischemic events, a phenomenon that has been observed in apneic individuals who develop a cardiac lesion that is less severe than those of patients with no OSA after a MI. 5 Considering the prevalence of OSA, as well as the importance of cardiovascular diseases, the objective of the present systematic review of the literature was to verify the association between OSA and MI.…”
Section: Introductionmentioning
confidence: 99%
“…21 This is probably because elderly patients, who have survived the long-standing hypoxia caused by OSA, become preconditioned for subsequent hypoxia better than young patients. 22 Similarly, in the case of chronic diseases, such as diabetes, hypertension, and dyslipidemia, people with long-term illnesses may be more resistant to OSA than those without these illnesses. 13 The most significant weakness of this study is that the adequacy of the diagnosis and the severity of disease could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%